Crise mundial e reestruturação produtiva: algumas questões de ordem teórica - MELLO, Alex Bolonha Fiúza de (2012)
The crisis of the accumulation pattern that supported the intensive capitalistic growth since post-war period until the beginning of the seventies has suscitated along the last decades some theoretical efforts to realize/explain the historical/sociological (economical/political) causes present in the root of this process as a whole. This paper aims to raise some questions of more general thoretical order, considering the fact that the new crisis, which is also a crisis of accumulation, occurs in the context of a capitalism organized in a global productive basis, what claims for new theoretical developments and new approachs respect to that has been called “new productive restructuration”.